Modulation of Biological Membranes Using Small-Molecule Compounds to Counter Toxicity Caused by Amyloidogenic Proteins - Raina Marie Seychell; Adam El Saghir; Neville Vassallo (Membranes)
The transition of peptides or proteins along a misfolding continuum from soluble functional states to pathological aggregates, to ultimately deposit as amyloid fibrils, is a process that underlies an expanding group of human diseases—collectively known as protein-misfolding disorders (PMDs). These include common and debilitating conditions, such as Alzheimer’s disease, Parkinson’s disease, and type-2 diabetes. Compelling evidence has emerged that the complex interplay between the misfolded proteins and biological membranes is a key determinant of the pathogenic mechanisms by which harmful amyloid entities are formed and exert their cytotoxicity. Most efforts thus far to develop disease-modifying treatments for PMDs have largely focused on anti-aggregation strategies: to neutralise, or prevent the formation of, toxic amyloid species. Herein, we review the critical role of the phospholipid membrane in mediating and enabling amyloid pathogenicity. We consequently propose that the development of small molecules, which have the potential to uniquely modify the physicochemical properties of the membrane and make it more resilient against damage by misfolded proteins, could provide a novel therapeutic approach in PMDs. By way of an example, natural compounds shown to intercalate into lipid bilayers and inhibit amyloid–lipid interactions, such as the aminosterols, squalamine and trodusquamine, cholesterol, ubiquinone, and select polyphenols, are discussed. Such a strategy would provide a novel approach to counter a wide range of toxic biomolecules implicit in numerous human amyloid pathologies.